THE CONFIGURATION OF RADICAL ISLAMISM IN INDONESIA: Some Contemporary Assessments and Trajectories - Hilmy, Masdar (IAIN Ponorogo, 2014)
This paper attempts at analyzing the configuration of radical Islamism in contemporary Indonesia. The basic argument developed throughout this paper is that the reality of radical Islamism will always exist as long as all necessary conditions are there. Adopting the opportunity structure theory, among the necessary conditions that lead to the birth and existence of radical Islamism are: 1) Islamist ideology derived from the sacred texts, the Qur’an and Sunnah; 2) socio-political setting and issues where Muslims live; 3) actors, the Islamists, who craft the logics of Islamist ideology based on the interplay between the issues prevalent in the Muslims’ socio-political setting and the ideology constructed from the sacred texts. This article is divided into parts as follows: 1) the streams in Islamist thought and movement; 2) the anatomy of radical Islamism; 3) the membership of radical Islamism, and 4) the trajectories of radical Islamism, before it is ended with concluding remarks.